Effects of pentagamavunon-0 on histaminemediated hyperresponsive airway in asthmatic models : in-vitro in-vivo - Agung Endro Nugroho; Hemmy Prasetyo; Djoko Suhardjono; Mulyono Zhang Be; Shuang Liu; Supardjan A. Margono; Kazutaka Maeyama (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Asthma is a chronic inflammatory airway disease involving reversible airway constriction and airway hyperresponsiveness (AHR) to allergens, airway edema, and increased mucus secretion tumor cells. To date, exploration of antiasthmatic drug is still being studied both from natural products or sinthetic processes. One of the sinthetic compound is pentagamavunon-0 (PGV-0) which possesses anti-inflammatory and inhibitory effects on histamine release from rat mast cells. The aim of the study is to look at the effects of PGV-0 on histaminemediated hyperresponsive airway in asthmatic models (in vitro and in vivo studies). In vitro study was conducted using isolated organ technique with isotonic transducer. The results have shown that PGV-0 could not inhibit the contraction of isolated guinea pig trachea induced by histamine. PGV-0 did not change the pD2 and Emax values of histamine on trachea smooth muscle. The finding indicates that PGV-0 does not have affinity and intrinsic activity on H-1 histaminergic receptor in trachea smooth muscle. In vivo study, we sensitized the rats with ovalbumin (OVA) to develop the airway hyperreactivity to histamine. Histamine level in bronchoalveolar lavage fluid (BALF) and airway tissue were determined using HPLC-fluorometry. Multiple exposures of ovalbumin significantly histamine level in BALF by 74.51±5.33 pmol/mL or 6-times higher than this of control saline group. Oral administration of PGV-0 (40 mg/kg BW) significantly decreased the histamine accumulation in BALF to 30 % of the value of control group in asthmatic rats. Besides, PGV-0 significantly prevented the histamine decrease in asthmatic rats to 37.8 % trachea, and 34.2 % in bronchus. However, PGV-0 did not succeed to prevent the histamine decrease in the lung of asthmatic rats. The result of the study may provide useful information for further discovering pharmacological synthetic compound for treatment of allergic inflammatory asthma.Key words: asthma, curcumin, pentamavunon-0, histamine, airway hyperresponsiveness